Pengembangan Media Little Picture Card (LPC) Materi Jamur Endofit Untuk Melatih Kemampuan Literasi Sains Mahasiswa Universitas KH. A. Wahab Hasbullah - Fariyanti, Ika; Meishanti, Ospa Pea Yuanita (EDUSCOPE: Jurnal Pendidikan, Pembelajaran, dan Teknologi, 2023)
ABSTRACT One of the materials in the General Biology course is Fungi in the Biology Education Program of KH University. A. Wahab Hasbullah. The teaching lecturer stated that the Fungi material required practical activities, but practicum facilities were not yet available. These problems can be overcome with the Little Picture Card (LPC) learning media. LPC media contains material and pictures so that it can explain the meaning of the concepts being studied. Therefore, researchers will develop the Little Pictur Card (LPC) learning media for endophytic fungi. The research objectives were: (1) to describe the feasibility of Little Picture Card (LPC) media on endophytic mushroom material, (2) to describe the feasibility of Little Picture Card (LPC) media, (3) to describe student responses to the attractiveness of Little Picture Card media ( LPC) on endophytic fungal material. This study uses the ADDIE research model. The research procedure went through 5 stages, namely: 1) analysis 2) design 3) development 4) implementation and 5) evaluation. Media validation was carried out by material experts and media experts, while response validation was carried out by 21 Biology Education study program students. The results showed that the Little Picture Card media performed by material experts and media experts, material experts showed the criteria of "Very Appropriate" with a percentage of 91.07%. The results of the media expert showed the criteria of "Very Appropriate" with a percentage of 95.00%. The results of the responses by 21 students obtained a percentage of 81.5% with "Interesting" criteria. This shows that the Little Picture Card media is suitable for use as a learning medium for General Biology courses and is attractive to students on the condition that further development research and wider trials are carried out, so that it is obtained that the Little Picture Card media has empirically tested validity and is ready to use. KEYWORDS: Little Picture Card, endophytic mushroom learning media, student literacy ABSTRAK Salah satu materi pada matakuliah Biologi Umum adalah Fungi di Progam Pendidikan Biologi Universitas KH. A. Wahab Hasbullah. Dosen pengampu menyatakan bahwa materi Fungi memerlukan kegiatan praktikumnamun sarana praktikum belum tersidia. Permasalahan tersebut dapat diatasi dengan media pembelajaran Little Picture Card (LPC). media LPC memuat materi dan gambar sehingga mampu menjelaskan makna konsep yang dipelajari. Oleh karena itu, peneliti akan mengembangkan media pembelajaran Little Pictur Card (LPC) materi jamur endofit. Tujuan penelitian adalah: (1) untuk mendeskripsikan kelayakan media Little Picture Card (LPC) pada materi jamur endofit, (2) untuk mendeskripsikan kelayakan media Little Picture Card (LPC), (3) untuk mendeskripsikan respon mahasiswa terhadap kemenarikan media Little Picture Card (LPC) pada materi jamur endofit. Penelitian ini menggunakan model penelitian ADDIE. Prosedur penelitian melalui 5 tahapan yaitu: 1) analysis 2) design 3) development 4) implementation dan 5) evaluation. Validasi media dilakukan oleh ahli materi dan ahli media sedangkan validasi respon dilakukan oleh 21 mahasiswa prodi Pendidikan Biologi. Hasil penelitian menunjukkan bahwa media Little Picture Card yang dilakukan oleh ahli materi dan ahli media, ahli materi menunjukkan kriteria “Sangat Layak” dengan persentase 91,07%. Hasil ahli media menunjukan kriteria “Sangat Layak” dengan presentase 95.00%. Hasil respon oleh 21 mahasiswa memperoleh presentase 81,5% dengan Kriteria “Menarik”. Hal ini menunjukan bahwa media Little Picture Card layak digunakan sebagai media pembelajaran mata kuliah Biologi Umum dan menarik bagi mahasiswa dengan syarat dilakukan penelitian pengembangan lebih lanjut dan uji coba yang lebih luas, sehingga diperoleh bahwa media Little Picture Card teruji validitasnya secara empiris dan siap digunakan Kata kunci : Little Picture Card, media pembelajaran jamur endofit, literasi mahasiswa